2014
DOI: 10.1038/ncomms4995
|View full text |Cite
|
Sign up to set email alerts
|

PADI4 acts as a coactivator of Tal1 by counteracting repressive histone arginine methylation

Abstract: The transcription factor Tal1 is a critical activator or repressor of gene expression in hematopoiesis and leukaemia. The mechanism by which Tal1 differentially influences transcription of distinct genes is not fully understood. Here we show that Tal1 interacts with the peptidylarginine deiminase IV (PADI4). We demonstrate that PADI4 can act as an epigenetic coactivator through influencing H3R2me2a. At the Tal1/PADI4 target gene IL6ST the repressive H3R2me2a mark triggered by PRMT6 is counteracted by PADI4, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 69 publications
(101 reference statements)
3
62
0
Order By: Relevance
“…28,29 Sequences of primer pairs used for ChIP-polymerase chain reaction (PCR) are available upon request. DNA recovery was calculated as percentage of the input.…”
Section: Chip Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 Sequences of primer pairs used for ChIP-polymerase chain reaction (PCR) are available upon request. DNA recovery was calculated as percentage of the input.…”
Section: Chip Assaysmentioning
confidence: 99%
“…30 Coimmunoprecipitation from K562 cells and transfected HEK293 cells and purification of TAL1 complexes for mass spectrometry were performed similarly as previously described 29 (see also supplemental Figure 5). …”
Section: Interaction Assaysmentioning
confidence: 99%
“…It has been proposed that PADIs could contribute to cancer by acting as coactivator of oncogenic transcription factors eliciting tumor-promoting expression programs. To illustrate this, PADI4 was shown to enhance transcriptional regulation of Tal1 in hematopoietic stem cells (17). However, the outcome of such a coactivator function is strongly dependent on the cellular context.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that PADI4 may target different histone arginines (32,33). Kolodziej et al previously identified PADI4 as a novel interaction partner of T-cell acute lymphocytic leukemia protein 1 (Tal1), which is a critical regulator of hematopoietic gene expression and may act as an oncogene if aberrantly expressed, and identified a large number of genes that are co-regulated by PADI4 and Tal1 (31). Overexpression of PADI4 is often observed in growth of tumors, and the inhibitor Cl-amidine reduces growth of a subset of cell lines (34).…”
Section: Decreased Expression Normal Expression Overexpression ------mentioning
confidence: 99%
“…Yao et al reported that there is an inverse correlation between the expression of Bmi-1 and p14ARF, and thereby dysfunction of the p53 growth regulatory pathway during the development of gastric cardia adenocarcinoma (42). In addition, a number of studies proposed that PADI4 plays an important role in various cellular processes, including proliferation, the cell cycle and apoptosis (27,(30)(31)(32)(33). PADI4 overexpression has also been considered to reduce the expression of p53-targeted genes, resulting in the disruption of cellular apoptosis and of the normal cell cycle (35,43,44).…”
Section: Decreased Expression Normal Expression Overexpression ------mentioning
confidence: 99%